Time-motion analysis and physiological demands in international women's team handball - Manchado, C.; Platen, P. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
We analyzed the horizontal movement pattern, including the sprint acceleration profiles, of individual female handball players of the Norwegian National Team and a German First League Team and the corresponding heart rates during a match. The results indicate that a high VO2max appears to be important in top-level international women`s handball. Sprint and endurance training should be conducted according to the specific demands of the player`s position.